How Archaeologists Can Effectively and Ethically Cultivate Responsible and Responsive Stewards. Issue 1 (February 2022) - Wright, Dennis L.
Abstract: The objective of this article is to share how professional archaeologists can leverage their knowledge and influence to develop collectors and amateur archaeologists into responsible and responsive stewards (RRS). This approach furthers the primary purposes of the National Historic Preservation Act as well as the ethics of the Society for American Archaeology. I share my own journey about finding artifacts in the Texas Panhandle, yearning to understand more about them, and how a poster in a gas station led me to visiting a local Stone Age Fair where I met a professional archaeologist. This archaeologist mentor was willing to answer my questions and guide me to greater understanding of archaeological ethics and practice, which prompted me to document everything I had found. In turn, I have shared my experience with many other nonprofessionals. Archaeologist mentors can have great influence if they are willing to meet collectors and amateur archaeologists on their level. Ultimately, collectors and archaeologists share a love of artifacts and a passion for the history behind them.